Pengolahan Ubi Jalar Ungu Menjadi Stik Sebagai Diversifikasi Pangan Desa Pagar Batu Bengkulu Selatan - Eka Dewi Anggraini; Ruspiani (UNIB Press, 2022)
This activities aims to help empower the community’s economy duting pandemic covid-19 in Pagar Batu Village, Seginim District, South Bengkulu. The potential resources in this village are abundant sweet potato plants, but the processing is still simple and the marketing process is not too extensive, causing the selling price of sweet potatoes to be not too high. The method used in this activities consists og three stages, namely preparation, implementation, and evaluation of activities. This activities was carried out on July 26th until August 8th 2021 which was attended by ten women and young women. The acticities of processing sweet potatoes into purple sweey potato sticks got a good response by the community. Many people are motivated to implement this product as a business opportunity to increasing their income from selling the product during pandemic.